Editorial: Post-COVID-19: How to prepare for the next pandemic - Edward Eremugo Kenyi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
South Sudan urgently needs a pandemic influenza preparedness strategy if we are to survive the next big one. COVID-19 was the wake-up call. Globally, as of April 2023, there were 764,474,387 confirmed cases of COVID-19, including 6,915,286 deaths. Although the COVID-19 pandemic did not cause so much devastation and deaths in many African countries, including South Sudan, it could have been worse, considering our poor health infrastructure and high poverty levels.